THE LOCAL WISDOM VALUE OF SHORT STORIES IN LITERARY STUDY AT SENIOR HIGH SCHOOLS AT BANDA ACEH - Hendra Kasmi; Millata Zamana (Getsempena English Education Journal, 2019)
Entitled with the local wisdom value in the short story of literature study in Senior High Schools' in Banda Aceh, this study was designed to investigate the local wisdom's value in the short story of literature study in Senior High Schools Banda Aceh. The study aims to know the value of local wisdom in the short story of Senior High Schools in Banda Aceh. The method deployed in this research is a descriptive analysis through a structural approach. The source of the study are the short stories in the literary study in Senior High School in Banda Aceh. The result of the study shows that the local wisdom being portrayed through the short stories in the literary study at senior high schools in Banda Aceh is rich with social, art, etiquette, and religious value. All the content in the short stories is a reflective entity of Acehnese people from time to time. The short stories in the literary study can improve students' understanding of the value in Acehnese local wisdom.